Diagnostic and Prognostic Value of JC Virus DNA in Plasma in Progressive Multifocal Leukoencephalopathy. (15th January 2018) - Ferretti, Francesca; Bestetti, Arabella; Yiannoutsos, Constantin T; Musick, Beverly S; Gerevini, Simonetta; Passeri, Laura; Bossolasco, Simona; Boschini, Antonio; Franciotta, Diego; Lazzarin, Adriano; Cinque, Paola
Abstract: Background: Progressive multifocal leukoencephalopathy (PML) is a severe demyelinating disease caused by the polyomavirus JC (John Cunningham; JCV) that affects patients with impaired immune systems. While JCV-DNA detection in cerebrospinal fluid (CSF) is diagnostic of PML, the clinical significance of plasma JCV-DNA is uncertain. Methods: We retrospectively analyzed plasma samples from PML patients that were drawn close to disease onset and from controls without PML. In PML patients, we compared plasma JCV-DNA detection and levels to clinical and laboratory parameters, and patient survival. Results: JCV-DNA was detected in plasma of 49/103 (48%) patients with PML (20/24, 83%, human immunodeficiency virus [HIV] negative; 29/79, 37%, HIV-positive) and of 4/144 (3%) controls without PML (0/95 HIV-negative; 4/49, 8%, HIV-positive), yielding a diagnostic sensitivity and specificity of 48% and 97% (83% and 100% in HIV-negative; 37% and 92% in HIV-positive), respectively. Among 16 PML patients with undetectable CSF JCV-DNA, 4 (25%) had detectable plasma JCV-DNA. Plasma JCV-DNA levels were independently associated with CSF levels ( P < .0001) and previous corticosteroid treatment ( P = .012). Higher plasma JCV-DNA levels were associated with disease progression in HIV-negative patients ( P = .005); in HIV-positive patients, there was an increased risk of progression only in those treated with combination antiretroviral therapy (cART; P < .0001). Conclusions: Testing JCV-DNA in plasma might complement PML diagnosis, especially when CSF is unavailable or JCV-DNA not detectable in CSF. In addition, JCV-DNA plasma levels could be useful as a marker of disease progression in both HIV-negative and cART-treated, HIV-positive PML patients. Abstract : Polyomavirus JC (JCV)-DNA assessment in plasma might complement progressive multifocal leukoencephalopathy (PML) diagnosis, especially when cerebrospinal fluid (CSF) is unavailable or JCV-DNA not detectable in CSF. In addition, JCV-DNA plasma levels could provide a marker of PML progression.